Restoring Asia’s roar: Opportunities for tiger recovery across the historic range - Gray, Thomas NE; Rosenbaum, Rachel; Jiang, Guangshun; Izquierdo, Pablo; Yongchao, JIN; Kesaro, Leoung; Lyet, Arnaud; Pasha, MKS; Patterson, David J.; Channa, Phan; Jinzhe, QI; Ripple, William J.; et al. (Frontiers in Conservation Science, 2023)
Wildlife conservation in the Anthropocene requires bold conservation solutions including restoration of ecosystems and species. The recovery of large carnivore populations is a conservation goal which can generate significant benefits in terms of ecosystem services, ecological functionality, and human well-being. Tigers Panthera tigris, Asia’s most iconic species, are currently restricted to less than 10% of their historic range with recent national extinctions from a number of countries in mainland Southeast Asia. Successful recovery of tigers requires expanding the species’ occupied range. Tiger range expansion needs suitable habitat, a robust prey base, and high levels of institutional support for conservation. We explored government support for conservation to produce a ranking of the political opportunities for tiger restoration across current and former tiger range countries. We used this analysis, in combination with globally remotely sensed data-sets on human impact, to show that there is potential for significant tiger range expansion with large expanses of currently unoccupied, but potentially suitable, habitat remaining in at least 14 countries including all extant tiger range countries and four countries with extirpated tiger populations – Cambodia, Lao PDR, Viet Nam, and Kazakhstan. Thirty-two percent of expansion areas were within 50-km, and 50% within 100-km, of current tiger populations highlighting that in many landscapes range expansion could be driven by the natural dispersal of tigers provided connectivity is maintained or enhanced. The proportion of potential range within existing protected areas varied between <5% in India, Indonesia, and China, to >60% in Thailand and Cambodia. As such socially appropriate conservation approaches, in collaboration with local communities, will be necessary to support tiger recovery in many areas. We recommend that some of the areas which we have identified should be highlighted as significant for future tiger conservation by tiger range country governments. Safeguarding these areas for human-carnivore coexistence, through targeted management of tigers, their prey, and land-use, could provide significant planetary benefits and support both tiger recovery and Global Sustainable Development Goals.